Aryl Hydrocarbon Receptor Activation Prevents Lung Ischemia Reperfusion Injury by Inhibiting ROS-triggered Ferroptosis in Mice - Peng Deng; Guanghua Xu; Li Wan; Jianwei Xu; Zuhuan Yao; Quanchao Sun (Current Molecular Medicine, 2026)
Introduction: Lung ischemia-reperfusion injury (LIRI) is a serious complication of lung transplantation that causes respiratory distress and is associated with high mortality. Ferroptosis, a novel form of programmed cell death, contributes to the pathogenesis of LIRI. The Aryl Hydrocarbon Receptor (AhR) is a ligand-activated transcription factor that regulates a variety of physiological functions. However, the role and mechanism of AhR in ferroptosis during LIRI after lung transplantation remain to be further investigated. Materials and Methods: AhR signaling and ferroptosis were examined in a mouse LIRI model and a pulmonary vascular endothelial cell line following hypoxiareoxygenation (H/R) culture. The severity of LIRI was assessed based on histological architecture and cytokine levels. Cell viability and damage were evaluated using the CCK-8 and LDH assays. Ferroptosis biomarkers, including Fe²⁷, malondialdehyde (MDA), reactive oxygen species (ROS), and glutathione (GSH), were measured using respective assay kits. PTGS2 (Prostaglandin-Endoperoxide Synthase 2), SLC7A11 (Solute Carrier Family 7 Member 11), and GPX4 (Glutathione Peroxidase 4) were analyzed by western blot. In vitro, lipid peroxidation was assessed by flow cytometry after DCFH-DA labeling. Transmission electron microscopy was used to observe mitochondrial ultrastructure. Results: Enhanced transcription of AhR and its downstream targets, CYP1A1 (Cytochrome P450 1A1) and CYP1B1 (Cytochrome P450 1B1), was observed. AhR deficiency exacerbated LIRI-induced ferroptosis and lung injury, whereas AhR activation mitigated lung injury and ferroptosis. H/R-induced cell injury and ferroptosis were alleviated by AhR activation. Increased ROS formation, primarily mitochondrial ROS (Mito-ROS), was triggered by AhR ablation or antagonism, and ROS inhibition subsequently reduced cell damage and ferroptosis. Discussion: Our findings indicate that AhR activation functions upstream by directly inhibiting excessive ROS accumulation triggered by I/R. This reduction in cellular oxidative stress prevents the lethal lipid peroxidation that drives ferroptosis. Conclusion: This study demonstrates the protective effect of AhR activation in LIRI by inhibiting ROS-induced ferroptosis, suggesting it may be a promising target for clinical prevention of LIRI.